Renal Oxygenation in the Pathophysiology of Chronic Kidney Disease - Liu, Zhi Zhao; Bullen, Alexander; Li, Ying; Singh, Prabhleen (Frontiers in Physiology, 2017)
Chronic kidney disease (CKD) is a significant health problem associated with high morbidity and mortality. Despite significant research into various pathways involved in the pathophysiology of CKD, the therapeutic options are limited in diabetes and hypertension induced CKD to blood pressure control, hyperglycemia management (in diabetic nephropathy) and reduction of proteinuria, mainly with renin-angiotensin blockade therapy. Recently, renal oxygenation in pathophysiology of CKD progression has received a lot of interest. Several advances have been made in our understanding of the determinants and regulators of renal oxygenation in normal and diseased kidneys. The goal of this review is to discuss the alterations in renal oxygenation (delivery, consumption and tissue oxygen tension) in pre-clinical and clinical studies in diabetic and hypertensive CKD along with the underlying mechanisms and potential therapeutic options.